Answer:
its 3
Step-by-step explanation:
selcet 3 it goes plus 3 then back to neg 4 its the 3rd option
Answer:
$32.07
ROUNDING ANSWER : $32
Step-by-step explanation:
you would subtract $44.95 -$12.88 which would give you $32.07
since you are rounding your answer would be $32
Hope this helps
Here is how we get the answer....
First, replace f(x) with y . ...
Replace every x with a y and replace every y with an x .
Solve the equation from Step 2 for y . ...
Replace y with f−1(x) f − 1 ( x ) . ...
Verify your work by checking that (f∘f−1)(x)=x ( f ∘ f − 1 ) ( x ) = x and (f−1∘f)(x)=x ( f − 1 ∘ f ) ( x ) = x are both true.
Answer:
1863/275=6.7745recurring
Step-by-step explanation:
Dont u have a calculator